HLA-A*68: 02-restricted Gag-specific cytotoxic T lymphocyte responses can drive selection pressure on HIV but are subdominant and ineffective - Kløverpris, H; Stryhn, A; Harndahl, M; Carlson, J; Leslie, A; Chen, F; Riddell, L; Mulenga, J; Walker, B; Ndung'U, T; Buus, S; Goulder, P (2013)
Background: Human leukocyte allele (HLA) class I polymorphism has the greatest impact of human genetic variation on viral load set point. A substantial part of this effect is due to the action of HLA-B and HLA-C alleles. With few exceptions the role of HLA-A molecules in immune control of HIV is unclear. Methods: We here study HLA-A-68:02, one of the most highly prevalent HLA-A alleles in C-clade infected sub-Saharan African populations, and one that plays a prominent role in the HIV-specific CD8+ T-cell responses made against the virus. Results: We define eight epitopes restricted by this allele and propose the peptide binding motif for HLA-A*68:02. Although one of these epitopes almost exactly overlaps an HLA-B*57-restricted epitope in Gag linked with immune control of HIV, this HLA-A*68:02-restricted Gag-TA10 response imposed only weak selection pressure on the virus and was not associated with significantly lower viral setpoint. The only HLA-A*68:02-restricted responses imposing strong selection pressure on HIV were in the flanking regions of Pol-EA8 and Pol-EA11 and within the Vpr-EV10 epitope (P=8×10-8). However, targeting of this latter epitope was associated with significantly higher viral loads (P=0.003), suggesting lack of efficacy. Conclusion: This study is consistent with previous data showing that HLA-A-restricted Gag-specific responses can impose selection pressure on HIV. In the case of HLAA-68:02 the Gag response is subdominant, and apparently has little impact in natural infection. However, these data suggest the potential for high frequency vaccineinduced Gag responses restricted by this allele to have significant antiviral efficacy in vaccine recipients. © 2013 Creative Common License.